Immunoassays for carbodiimide modified DNA-detection of unpairing transitions in supercoiled ColE1 DNA. - Wani, A A (1989)
The water soluble reagent N-cyclohexyl-N'-beta-(4-methylmorpholinium) ethyl carbodiimide-p-toluene sulphonate (CMC) can be used to probe for unpaired and mismatched sites in DNA. Polyclonal antibodies for CMC modified DNA were produced in order to develop immunological assays for the localization and quantitation of CMC adducts. Immunoslot blot analysis of modified DNA exhibited antibody binding proportional to the extent of CMC modification with adduct detection in the femtamole range. Unmodified DNA did not cross react under the conditions of the assay. The distribution of CMC reactivity for supercoiled ColE1 DNA modified at 100, 200 and 300 mM NaCl was determined by immunoanalysis of EcoRI-Hae2-NruI restriction fragments Southern transferred to nylon membranes. Reactivity above random expectation occurred in the A2-II fragment which can be accounted for by its high A-T content of 71.3%. Reactivity below random expectation occurred in the C fragment which can be accounted for by its low AT content of 43%. CMC modification for the other restriction fragments appeared random.